Cefuroxime compared to piperacillin/tazobactam as empirical treatment of Escherichia coli bacteremia in a low Extended-spectrum beta-lactamase (ESBL) prevalence cohort - Thønnings, Sara (Infect Drug Resist, 2019)
Objectives: On January 18, 2010, a part of the capital region of Denmark shifted the empirical treatment of febrile conditions from cefuroxime to piperacillin/tazobactam. We compare empirical treatment with piperacillin/tazobactam versus cefuroxime for Escherichia coli bacteremia with regard to 14 days mortality, in a low prevalence cohort of Extended-spectrum beta-lactamase-producing E. coli. Methods: From January 18, 2010 to December 31, 2012, we conducted a retrospective cohort study including patients with E. coli bacteremia from six university hospitals in Copenhagen, Denmark. Clinical and laboratory information was obtained from a bacteremia research database, including information on comorbidity, and we used Cox proportional hazard analysis to asses all-cause 14 days mortality. Results: A total of 568 patients receiving either cefuroxime (n=377) or piperacillin/tazobactam (n=191) as empirical therapy were included. In the Cox proportional hazard model, cefuroxime treatment was significantly associated with death (mortality rate ratio 3.95, CI 1.12–13.90). Other variables associated with death were health care related infection (MRR 3.20, CI 1.67–6.15), hospital-acquired infection (MRR 2,17, CI 1.02–4.62), admission at intensive care unit (MRR 20.45, 5.31–78.82), and combination therapy with ciprofloxacin (MRR 2.14, CI 0.98–4.68). Conclusion: Empiric cefuroxime treatment of E. coli bacteremia was significantly associated with higher 14 days mortality in comparison with piperacillin/tazobactam.